Digital twins: Representation, Replication, Reality, and Relational (4Rs). (January 2022) - Hyre, Anna; Harris, Gregory; Osho, John; Pantelidakis, Minas; Mykoniatis, Konstantinos; Liu, Jia
Abstract: Digital twins hold promise for operational improvement for manufacturers. The use of digital twins in industry requires a significant change in manufacturing practices but is crucial to implementing smart manufacturing technologies and Industry 4.0 principles. Unfortunately, there is no consensus definition of a digital twin which leads to confusion about its essential features and distinction from product models and simulations. This research addresses the confusion surrounding digital twins by creating a generalized framework for creating a digital twin of any system, providing structure to improve communications about the digital twin, and aligning the digital twin's capabilities with its intended purpose.